Reassessing the schedule of the sugar season in maple under climate warming - de Lima Santos, Gian; Silvestro, Roberto; Kurokawa, Sara Yumi Sassamoto; de Lafontaine, Guillaume; Rossi, Sergio (Frontiers in Agronomy, 2025)
Daily temperature fluctuations trigger physical and metabolic processes in the xylem, affecting the timing and yield of maple sap production. This study evaluates sap production dynamics, examining the effects of mean monthly temperatures and freeze-thaw cycles before and during the sugar season. We developed a predictive model estimating sap phenology, i.e. the timings of sap season and their climatic drivers, under future warming scenarios in Quebec, Canada. We collected air temperatures and daily sap production at four study sites in 2022 and 2023 using rain gauges for simulating a gravity collection of sap. We estimated sap phenology using a neural network model based on average monthly temperatures. The length of the sugar season was consistent across and within sites, with the highly productive days showing similar occurrence across sites. Sap yields ranged from 9.28 to 23.8 liters in 2022 and 3.8 to 13.6 liters in 2023. Freeze-thaw events occurred on 64% of the days when sap was exuded. Our neural network model predicted that a 2°C increase in mean monthly temperatures would advance the sugar season start by 17 days and end by 13 days. Any mismatch between tapping and favorable weather conditions can significantly reduce sap production. With climate change, producers will be forced to progressively readjust the schedule of their field activities and tapping to match the shifting sugar season.